2018
DOI: 10.1519/jsc.0000000000002112
|View full text |Cite
|
Sign up to set email alerts
|

Low-Volume High-Intensity Interval Versus Continuous Endurance Training: Effects on Hematological and Cardiorespiratory System Adaptations in Professional Canoe Polo Athletes

Abstract: Sheykhlouvand, M, Gharaat, M, Khalili, E, Agha-Alinejad, H, Rahmaninia, F, and Arazi, H. Low-volume high-intensity interval versus continuous endurance training: effects on hematological and cardiorespiratory system adaptations in professional canoe polo athletes. J Strength Cond Res 32(7): 1852-1860, 2018-The aim of this study was to compare the effect of 2 paddling-based high-intensity interval training (HIIT) and continuous endurance training (CET) on hematological, immunological, and cardiorespiratory adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…However, no scientific literature regarding the relative impact of the emotional and psychological characteristics of these athletes is available. Several studies mainly investigated the anthropometric [ 35 ], nutritional [ 36 ], hormonal [ 37 ], and physiological [ 38 , 39 ] requirements of male and female canoe polo players. The research highlighted that many functional alterations in both men and women players result from basic differences in body size and body composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, no scientific literature regarding the relative impact of the emotional and psychological characteristics of these athletes is available. Several studies mainly investigated the anthropometric [ 35 ], nutritional [ 36 ], hormonal [ 37 ], and physiological [ 38 , 39 ] requirements of male and female canoe polo players. The research highlighted that many functional alterations in both men and women players result from basic differences in body size and body composition.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding training intervention, the included studies used a diversity of modalities and IT protocols. Most used cycling ( n = 18) or running ( n = 11), while some studies used walking [ 62 , 64 ], arm-cycling [ 52 ], paddling [ 60 , 65 ] and swimming [ 58 ]. Twenty-five studies involved exclusively submaximal IT protocol (i.e., HIIT), 10 studies involved exclusively maximal IT protocol (i.e., SIT), usually Wingate-based protocols (i.e., repeated 30 s “all-out” effort) and one study involved both submaximal and maximal protocols [ 44 ], and compared different rest interval mode (e.g., passive or active) for HIIT and SIT.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of HIIT protocols was prescribed and controlled based on percentage of maximal velocity achieved during incremental test (Vmax) [ 29 , 30 , 46 , 60 , 61 ], velocity associated with O 2max [ 43 , 59 ] or O 2peak [ 65 ], percentage of O 2max [ 50 , 55 , 56 , 57 , 67 ], or reserve oxygen uptake ( O 2reserve ) [ 62 , 64 ], percentage of HR max [ 41 , 66 ] or reserve heart rate HR reserve [ 42 ], and percentage of peak power [ 25 , 26 , 44 , 51 , 58 ] or maximum anaerobic power [ 27 ]. Eleven studies prescribed SIT protocol using “all out” efforts [ 22 , 23 , 24 , 44 , 45 , 47 , 48 , 52 , 53 , 54 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there is growing evidence claiming that physical activities stimulate the immune function and slow down the immunosenescence phenomenon [ 43 ]. In terms of the influence exerted by the type of exercise, a comparative study showed that continuous endurance training caused a decrease in lymphocyte count as opposed to high-intensity interval training, while all the other leukocyte fractions showed no significant variations [ 45 ].…”
Section: Leukocytesmentioning
confidence: 99%